Business English and communication - Stewart, Marie M., 1899-; Zimmer, Kenneth, 1921-; Clark, Lyn. (New York : Gregg Division/McGraw-Hill, 1984)
Emphasizes the English and communication skills that are necessary in the business world, including speaking, listening, reading, and writing.
Rev. ed. of: Business English and communication / Marie M. Stewart ... [et al.]. 5th ed. c1978.
Includes index.
Keywords: English language -- Business English; English language -- Business English; Business education